The Oxford handbook of the economics of the biopharmaceutical industry - Danzon, Patricia Munch, 1946-; Nicholson, Sean. (New York ; Oxford : Oxford University Press, 2012)
This examination of the economics of the biopharmaceutical industry has 18 chapters by health economists. Part 1 examines the economics of biopharmaceutical innovation. Part 2 examines the market for biopharmaceuticals with chapters on prices and reimbursement in industrialised and developing countries.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Pharmaceutical industry; Biopharmaceutics -- Economic aspects